Maternal Phthalate Exposure Alters Prostate Proteome in Rat Offspring: Linking Omics Insights to Prostate Cancer Risk in Humans - Souza, Patrick Vieira [UNESP]; Aquino, Ariana Musa [UNESP]; Alonso-Costa, Luiz Guilherme [UNESP]; Magosso, Natália [UNESP]; Oliveira, Marcos Antonio Fernandes de [UNESP]; Rocha, Vanessa Aguiar [UNESP]; Fioretto, Matheus Naia [UNESP]; Moreira, Mirella Franco [UNESP]; Pinha, Victória Cristina [UNESP]; Caxali, Gabriel Henrique [UNESP]; Justulin, Luis Antônio [UNESP]; Flaws, Jodi Anne; et al. (Elsevier, 2025)
BACKGROUND: Phthalates are compounds used as plasticizers to increase the flexibility of plastics and are considered endocrine disruptors. Some studies suggest that the origin of prostate cancer (PCa) may be associated with disturbances during embryo-fetal development. Previous data showed that perinatal exposure to the same phthalate mixture (PM) used here increased the incidence of adenocarcinomas in the prostates of aged rats. Building on our earlier work, this study identifies proteins altered in the prostate proteome by exposure to a PM during gestation and lactation in rats, focusing on proteins in the human secretome and their correlation with PCa. METHODS: Pregnant SD rats were divided into three groups and treated from gestational day (GD)10 to postnatal day (PND)21. On PND22 the differentially abundant proteins in the offspring's prostate were compared with the predicted secreted proteins in humans. Then, the abundance of selected proteins was compared among groups and enriched. Finally, a protein-protein interaction network was obtained. The resulting data were cross-referenced with data for PCa and some targets were validated by RT-qPCR and Western blot. RESULTS: Perinatal exposure to PM affected the endoplasmic reticulum, decreasing the amount of certain proteins crucial for protein folding and secretion, impairing secretion of several proteins important for proper prostate development. Furthermore, in silico analysis revealed that several proteins in the rat proteome are also altered in patients with PCa. CONCLUSIONS: Our results suggest that early exposure to phthalates may modulate protein secretion, creating a microenvironment that impairs tissue development and increases susceptibility to oncogenesis.